Great Modern Short Stories: An Anthology of Twelve Famous Stories and Novelettes - Bennett A. Cerf (USA Random House, 1942)
selected, and with a foreword and biographical notes by Bennett A. Cerf, 1898-1971 Editor of The Modern Library
Five English stories: Heart of darkness, by Joseph Conrad. The apple-tree, by John Galsworthy. The Prussian officer, by D. H. Lawrence. Miss Brill, by Katherine Mansfield. The letter, by W. S. Maugham.--Seven American stories: The snows of Kilimanjaro, by Ernest Hemingway. Paul's case, by Willa Cather. I'm a fool, by Sherwood Anderson. Haircut, by Ring Lardner. Turn about, by William Faulkner. The old demon, by Pearl S. Buck. The red pony, by John Steinbeck.
Keywords: Literature (3GdCOHs; General; Short stories